Смарт-спеціалізація промислових регіонів України: організаційно-економічний супровід - Підоричева, І.Ю.; Баш, А.С. (Економіка промисловості, 2024)
Промислові регіони України, особливо прифронтові (Донецька, Луганська, Харківська і Запорізька області), зазнали найбільших збитків і втрат внаслідок повномасштабної війни. Потреби на їх відновлення, за спільною оцінкою міжнародних інституцій та уряду України, складають половину (50,46% або 207,2 млрд доларів США) потреб на відбудову України. Зважаючи на структурну відсталість економіки промислових регіонів, у якій переважають галузі зі слабкою інноваційною активністю та низькою технологомісткістю, продовження довоєнних траєкторій їх розвитку є абсолютно неприйнятним і неконкурентним на тлі розгортання у світі Індустрії 4.0-5.0. В умовах істотної зміни профілів промислових регіонів через війну з’являється шанс відродити їх економіку, але вже на принципово нових, інноваційних, засадах. Для цього може бути використаний підхід смарт-спеціалізації, націлений на структурну трансформацію економіки та розвиток на цій основі нових конкурентних переваг регіонів і країн. Наголошено на необхідності проведення критичного аналізу та переосмислення напрямів імплементації підходу смарт-спеціалізації в промислових регіонах України, що зумовлено різним ступенем врахування його основних засад в стратегіях регіонального розвитку на 2021-2027 рр. та потребою у структурній перебудові їх економік, подоланні наслідків війни для місцевого населення.
Метою статті є ідентифікація ключових проблем у сфері організаційно-економічного забезпечення реалізації підходу смарт-спеціалізації у промислових регіонах України та визначення шляхів їх вирішення з урахуванням суто українських викликів і досвіду ЄС.
Обґрунтовано роль організаційно-економічного супроводу імплементації підходу смарт-спеціалізації в національних умовах. Поглиблено наукові уявлення про основні організаційно-економічні проблеми та недоліки імплементації підходу смарт-спеціалізації в промислових регіонах України. Звернуто увагу, що замороження цих проблем та відсутність відповідних дій щодо їх усунення унеможливить структурно-інноваційні перетворення в економіці регіонів на засадах сталого розвитку і, як наслідок, виключить можливість подолання їх структурної відсталості. Обґрунтовано пропозиції щодо шляхів вирішення існуючих організаційно-економічних проблем з урахуванням суто українських викликів, а також знань, одержаних в країнах-членах ЄС при реалізації цього підходу протягом останніх десяти років. Практична реалізація цих пропозицій дасть змогу скоригувати смарт-орієнтовані цілі та секторальні фокуси стратегій регіонального розвитку, спрямувати стратегії на трансформацію економіки промислових регіонів через підтримку секторів і галузей, які мають потенціал розвитку нових конкурентних переваг. Industrial regions of Ukraine, especially near-front territories (Donetsk, Luhansk, Kharkiv and Zaporizhzhia regions), suffered the greatest damage and losses as a result of the full-scale war. The needs for their recovery, according to the joint assessment of international institutions and the Ukrainian government, constitute half (50.46% or $207.2 billion USD) of the reconstruction needs for Ukraine. Considering the structural lag of the economy in industrial regions, dominated by sectors with weak innovation activity and low technological intensity, the continuation of pre-war development trajectories is absolutely unacceptable and non-competitive in the context of the Industry 4.0-5.0 which gains traction globally. In the conditions of a significant change in the profiles of industrial regions due to the war, there is an opportunity to revive their economy but on fundamentally new, innovative principles. Smart specialization can be utilized for this purpose, aiming at the structural transformation of the economy and the development of new competitive advantages for regions and countries. Emphasis is placed on the necessity of conducting a critical analysis and rethinking the implementation directions of smart specialization in the industrial regions of Ukraine. This is due to the varying degrees of consideration of its fundamental principles in the regional development strategies for 2021-2027 and the need for the structural transformation of their economies to overcome the consequences of the war for the local population.

The purpose of the article is to identify key problems in the field of organizational and economic support for the implementation of the smart specialization approach in the industrial regions of Ukraine and to determine ways to solve them, taking into account purely Ukrainian challenges and EU experience.

The role of organizational and economic support for the implementation of the smart specialization approach in national conditions has been substantiated. The scientific understanding of the main organizational and economic problems and shortcomings of the implementation of the smart specialization approach in the industrial regions of Ukraine has been deepened. It is highlighted that freezing these problems and the absence of appropriate actions to address them will prevent structural and innovation transformations in the economies of regions based on the principles of sustainable development, thereby excluding the possibility of overcoming their structural backwardness. Proposals on ways to solve existing organizational and economic problems are substantiated, taking into account purely Ukrainian challenges, and the knowledge obtained in the EU member states during the implementation of this approach over the last ten years. The practical implementation of these proposals will make it possible to adjust the smart-oriented goals and sectoral focuses of regional development strategies, to direct them to the transformation of the economy of industrial regions through the support of sectors and industries that have the potential to develop new competitive advantages.